Hydatidiform Mole Types and Age Demographics in Sindh Province, Pakistan - Parsa Kainat, Muhammad Rahil Khan, Suresh Kumar, Fida Hussain, Abdul Aziz Shaikh, Maryam Anmol (Pakistan Journal of Medical & Health Sciences, 2023)
Hydatidiform mole can be classified as partial and complete depending on the clinical and histopathological features. There is regional variation in incidence of hydatidiform mole with more cases seen in Asia, Africa and other developing countries. This cross-sectional descriptive study was done at the department of histopathology in Diagnostic and research laboratory Hyderabad Sindh. A total of 261 cases were added in the study including 251 cases of suction and evacuation and 10 cases of hysterectomy. The mean age was 27.16±6.66 with age range of 17-60 years. In our study out of 260 samples, 155(59.6%) were of complete mole while 105(40.4%) were of partial mole. The incidence of mole was highest in the age group 26-30 years. The prevalence of hydatidiform mole was notably higher in comparison to numerous other studies. In conclusion, it is recommended that all abortion specimens undergo evaluation to prevent misdiagnosis of gestational trophoblastic disease and to ensure appropriate treatment and follow-up, thereby minimizing the risk of complications. Keywords: Hydatidiform mole. Complete mole. Partial mole. Molar pregnancy.